Empowering Rural Students: Evaluating the Effectiveness of Offline English Verb Applications - Rahayu, Sri; Sampelolo, Rigel (Publikasi dan UKI Press UKI Toraja., 2024)
This study explores the effectiveness of an offline English verb application in enhancing the English proficiency. Utilizing a quantitative approach, the research involved administering a written test consisting of 25 multiple-choice questions both before (pre-test) and after (post-test) the intervention. The test questions were of equal difficulty to ensure consistency. A purposive sampling technique was employed to select a single class of 23 students from rural backgrounds as the sample. The findings indicate that the English verb application significantly improved students' vocabulary, as evidenced by notable differences in pre-test and post-test scores. This study highlights the potential of offline educational tools to bridge learning gaps and empower students in underserved areas.